Understanding women's empowerment and its determinants in post-communist countries: Results of Azerbaijan national survey. (May 2017) - Habibov, Nazim; Barrett, Betty Jo; Chernyak, Elena
Abstract: Using data from 1451 women from the Azerbaijan Demographic and Health Survey (AZDHS), the present study provided an evaluation of Kishor's (2000) framework for women's empowerment through an investigation of the relationship between four sources of empowerment (education, relative education compared to partner, relative earnings compared to partner, wealth index) and five settings of empowerment (age, population density, region of residence, community education, and community wealth) on the level of evidence of women's empowerment in three areas (women's participation in household decision making, attitudes towards wife beating, and women's ability to refuse sexual intercourse). Findings suggest that the relationship between sources, settings, and evidence of empowerment is at times paradoxical, particularly for women who achieve equal or higher educational or earning status in relation to their male partners. Implications of these findings for the further refinement of theoretical models of women's empowerment which centralize an analysis of patriarchy are provided. Highlights: We analyzed survey data drawn from 1451 women in Azerbaijan. Investigated relationship between sources, settings, and evidence of empowerment. Education emerged as the most salient predictor of evidence of women's empowerment. Surpassing partners in education or earnings inhibited female sexual empowerment. Empowerment may be more complicated than sole reliance on benchmarks reveal.